Immune Response, Viral Shedding Time, and Clinical Characterization in COVID-19 Patients With Gastrointestinal Symptoms - Yang, Huan; Xi, Xiangyu; Wang, Weimin; Gu, Bing (Frontiers in Medicine, 2021)
BACKGROUND & AIMS: Gastrointestinal symptoms (GI symptoms) are frequent coronavirus disease (COVID-19) symptoms. Previous studies mainly focused on epidemiology and characteristics in patients with GI symptoms, little is known about the roles of immune response in susceptibility to and severity of infection. Here, we analysed COVID-19 cases to determine immune response and clinical characterization in COVID-19 patients with GI symptoms. METHODS: According to whether they had GI symptoms, patients were divided into GI and non-GI groups. The clinical characteristics, selected laboratory abnormalities, immune response, treatment and clinical outcome were compared between the patients with or without GI symptoms. RESULTS: 25% of patients reported at least one gastrointestinal symptom. The rates of fatigue (65% vs 23.7%; p=0.001), increased LDH (45% vs 20.3%; p=0.031), increased CK (25% vs 1.7%; p=0.004) and bilateral pneumonia (90% vs 61.9%; p=0.018) were significantly higher in patients with GI symptoms. The percentages of increased neutrophil-to-lymphocyte ratio (NLR, cut off 3.04, 55.5% vs 31.7%; p=0.047), lymphopenia (55.5% vs 31.7%; p=0.047), increased serum amylase (SAA, 75% vs 38.5%; p=0.059), increased C-reactive protein (CRP, 58.3% vs 26.9%; p=0.061) . The clinical type on admission of patients with GI symptoms reported significantly higher rates of critical type (20% vs 3.3%; p=0.033). CONCLUSIONS: Our study provided the first quantitative data of immune activation profile on COVID-19 patients with GI symptoms. COVID-19 patients with GI symptoms showed more intense dysregulation of immune response than those without GI symptoms. Moreover, COVID-19 patients with GI symptoms were more likely to develop into critical type.